"When in Doubt, Ask the Patient": A Quantitative, Patient-Oriented Approach to Formative Assessment of CanMEDS Roles - Ashley Esteves; Meghan McConnell; Emanuela Ferretti; Adam Garber; Karen Fung- (Association of American Medical Colleges, 2021)
Introduction Since the introduction of competency-based frameworks into postgraduate medical curricula, educators have struggled to implement robust assessment tools that document the progression of necessary skills. The global movement towards competency-based medical education demands validated assessment tools. Our objective was to provide validity evidence for the Ottawa CanMEDS Competency Assessment Tool (OCCAT), designed to assess clinical performance in the communicator, professional, and health advocate CanMEDS roles. Methods We developed the OCCAT, a 29-item questionnaire informed by specialty-specific Entrustable Professional Activities and consultation with stakeholders, including patients. Our sample included nine neonatal-perinatal medicine and maternal fetal medicine fellows rotating through antenatal high-risk clinics at the Ottawa Hospital. Following 70 unique encounters, the OCCAT was completed by patients and learners. Generalizability theory was used to determine overall reliability of scores. Differences in self and patient ratings were assessed using analyses of variance. Results Generalizability analysis demonstrated that both questionnaires produced reliable scores (G-coefficient > 0.9). Self-scores were significantly lower than patient scores across all competencies, F(1, 6) = 13.9, p = .007. Variability analysis demonstrated that trainee scores varied across all competencies, suggesting both groups were able to recognize competencies as distinct and discriminate favorable behaviors belonging to each. Discussion Our findings lend support to the movement to integrate self-assessment and patient feedback in formal evaluations for the purpose of enriched learner experiences and improved patient outcomes. We anticipate that the OCCAT will facilitate bridging to competency-based medical education.